IMPLEMENTASI SENSOR MULTI-MODAL MENGGUNAKAN RASPBERRY PI DAN ROBOT OPERATING SYSTEM PADA SISTEM KEAMANAN RUMAH - I Wayan Suparno; Abdul Jalil (Electro Luceat, 2021)
The purpose of this study to build a Sensor Multi-Modal (SMM) can be used for home security system using Raspberry Pi hardware and Robot Operating System (ROS) software. SMM is the combination of several types of sensors into one unit to becomes a new module sensor. Sensors used in this study are PIR sensor, PING sensor, DHT11 sensor, IR sensor, fire sensor, and camera. The method used to connect the sensors are based on the communication of ROS nodes that processes using Arduino Uno and Raspberry Pi. ROS is a robot control software can be used to control the hardware and devices for embedded system. The Arduino Uno function in this study is low-level hardware used to read the sensors data, then sent the data to the Raspberry Pi to process the sensor data using ROS software. This study result is the implementation of SMM for home security system where this device can give a warning in the form of a buzzer when this SMM detect the object motion and fire.